25 Years of road safety: The journey from thinking humans to systems-thinking. (January 2022) - McIlroy, Rich C.; Banks, Victoria A.; Parnell, Katie J.
Abstract: Research into road safety has evolved from individual level component analysis to a much broader, systemic approach that acknowledges the fusion of 'socio' and 'technical' system elements. Over the past four decades, Professor Neville Stanton has contributed to over 179 journal articles, book chapters and conference papers in the field of road safety. The journey from 'thinking humans' to 'systems thinking' is demonstrated in this paper through the novel application of the Risk Management Framework (RMF) to the categorisation of research activities. A systematic review of Neville's contributions to the field of road safety demonstrates that over the years, his research activities have evolved from investigating single technological or human performance aspects in isolation (e.g., in-vehicle information design and workload) through to the holistic analysis of much broader systems (e.g., investigating road safety as a whole). Importantly, this evolution goes hand in hand with a change in the focus and emphasis of recommendations for improvements to safety. Going forward, Neville has helped pave the way for fundamental changes and improvements to be made to road safety systems around the world. Highlights: We review the past 25 years of Neville Stanton's contribution to road safety research. Articles are categorised according to the Risk Management Framework and the methods used. Over time, focus has moved from individuals (and their equipment) to whole systems. Recommendations for safety improvements have become wider reaching as system thinking has become the dominant perspective. Challenges remain in bridging the research-practice gap, but opportunities also exist.